Mengisi Kekosongan Perlindungan Hak Konstitusional: Kajian Urgensi Constitutional Complaint di Indonesia - Adhi Putra Satria (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2026)
ABSTRACT; This study aims to analyze the reasons why the concept of constitutional complaint has not yet been accommodated within the Indonesian legal system and to examine the urgency and prospects of its regulation as a protective instrument against violations of citizens’ constitutional rights. The primary issue addressed in this study is the limited constitutional protection mechanism available for violations of citizens’ rights arising from concrete actions of state officials, judicial decisions, and administrative policies that cannot be addressed through the judicial review mechanism before the Constitutional Court. The findings reveal that the absence of constitutional complaint within the national legal system is caused by normative limitations under Article 24C of the 1945 Constitution of the Republic of Indonesia, which restrictively defines the authority of the Constitutional Court, political legal constraints related to concerns over judicial supremacy, institutional structural issues between the Constitutional Court and the Supreme Court, as well as a legal culture that remains predominantly legalistic and formalistic. On the other hand, the regulation of constitutional complaint possesses significant urgency in strengthening the protection of citizens’ constitutional rights, constitutional supremacy, the principle of due process of law, and access to justice within a democratic rule of law state. The prospects for its regulation are considered relatively promising in line with the development of constitutional democracy, the strengthening of human rights protection, and the increasing demand for effective constitutional remedies. This study concludes that constitutional complaint constitutes an essential necessity in reformulating Indonesia’s constitutional system in order to address the gap in the protection of citizens’ constitutional rights. Therefore, regulatory reforms and the strengthening of constitutional culture are required to ensure the effective implementation of constitutional complaint as an instrument for the protection of constitutional rights within the Indonesian legal system.